A dynamic covalent polymeric antimicrobial for conquering drug‐resistant bacterial infection. Issue 5 (23rd May 2022) - Huang, Fan; Cai, Xiaoyao; Hou, Xiaoxue; Zhang, Yumin; Liu, Jinjian; Yang, Lijun; Liu, Yong; Liu, Jianfeng
Abstract: Increasing bacterial drug resistance to antibiotics has posed a major threat to contemporary public health, which resulted in a large number of people suffering from serious infections and ending up dying without any effective therapies every year. Here, a dynamic covalent polymeric antimicrobial, based on phenylboronic acid (PBA)‐installed micellar nanocarriers incorporating clinical vancomycin and curcumin, is developed to overcome drug‐resistant bacterial infections. The formation of this antimicrobial is facilitated by reversible dynamic covalent interactions between PBA moieties in polymeric micelles and diols in vancomycin, which impart favorable stability in blood circulation and excellent acid‐responsiveness in the infection microenvironment. Moreover, the structurally similar aromatic vancomycin and curcumin molecules can afford π–π stacking interaction to realize simultaneous delivery and release of payloads. In comparison with monotherapy, this dynamic covalent polymeric antimicrobial demonstrated more significant eradication of drug‐resistant bacteria in vitro and in vivo due to the synergism of the two drugs. Furthermore, the achieved combination therapy shows satisfied biocompatibility without unwanted toxicity. Considering various antibiotics contain diol and aromatic structures, this simple and robust strategy can become a universal platform to combat the ever‐threatening drug‐resistant infectious diseases. Abstract : A dynamic covalent polymeric antimicrobial, based on phenylboronic acid‐installed micellar nanocarriers incorporating vancomycin and curcumin, was developed to overcome drug‐resistant bacterial infections. Compared with monotherapy, this antimicrobial displayed more significant eradication of drug‐resistant bacteria in vitro and in vivo. This work could become a universal platform to combat the ever‐threatening drug‐resistant infectious diseases.